2011
DOI: 10.1134/s0006297911070121
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and biological significance of Yersinia pestis lipopolysaccharide biosynthesis genes

Abstract: In silico analysis of available bacterial genomes revealed the phylogenetic proximity levels of enzymes responsible for biosynthesis of lipopolysaccharide (LPS) of Yersinia pestis, the cause of plague, to homologous proteins of closely related Yersinia spp. and some other bacteria (Serratia proteamaculans, Erwinia carotovora, Burkholderia dolosa, Photorhabdus luminescens and others). Isogenic Y. pestis mutants with single or double mutations in 14 genes of LPS biosynthetic pathways were constructed by site-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 60 publications
1
51
3
Order By: Relevance
“…Not surprisingly, Anisimov and coworkers found a correlation between susceptibility to polymyxin B and the aminoarabinose content of Y. pestis lipid A (1). And recently, the contribution of aminoarabinose to polymyxin B resistance in Y. pestis has been conclusively demonstrated (19).…”
mentioning
confidence: 96%
“…Not surprisingly, Anisimov and coworkers found a correlation between susceptibility to polymyxin B and the aminoarabinose content of Y. pestis lipid A (1). And recently, the contribution of aminoarabinose to polymyxin B resistance in Y. pestis has been conclusively demonstrated (19).…”
mentioning
confidence: 96%
“…The lipid A structures of 10013 (⌬lpxP32) and 10031 (⌬rfaC725) (see Fig. S3 and S4 in the supplemental material) were consistent with Y. pestis 231 with an lpxP deletion and a waaC (rfaC) deletion as described by Anisimov et al (47,48). Results showed that there were no significant differences in LcrV levels in whole-cell lysates or in YopM secretion in each of the strains tested, except that the LcrV secretion level was significantly reduced in 10031(pCD1Ap) (see Fig.…”
Section: Mutant Construction and Lipid A Analysismentioning
confidence: 60%
“…4B). Dentovskaya et al reported that Pla activity was totally abolished in the Y. pestis 231 waaC (rfaC) mutant (48). Pla is an outer membrane protein and plasminogen activator, and its level of synthesis would be expected to affect its activity.…”
Section: Mutant Construction and Lipid A Analysismentioning
confidence: 99%
“…LPS is the major component of the outer membrane of Gramnegative bacteria and is a surface structure encountering the surrounding environment. The LPS of Y. pestis is O antigen deficient and restricted to the core and lipid A moieties (22). Much of the available detailed information about the receptors of Y. pestis phages focuses on the LPS (15,23).…”
mentioning
confidence: 99%
“…Much of the available detailed information about the receptors of Y. pestis phages focuses on the LPS (15,23). The LPS of Y. pestis has been studied extensively in terms of structure, activity, composition, modification, virulence, and assembly (15,(22)(23)(24). The receptor was identified as the LPS of Y. pestis for eight bacteriophages, including L-413C, P2 vir1, PhiJA1, PhiA1122, Pokrovskaya, T7 Yp , Y, and PST (23).…”
mentioning
confidence: 99%